MUTIARA WELIRANG VILLAGE-OWNED ENTERPRISE'S STRATEGY IN DEVELOPING SUMBER GEMPONG RICE FIELD TOURISM - Putri, Maulidiva Arisia; Sukmana , Hendra (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the strategy of the Mutiara Welirang Village-Owned Enterprise (BUMDes) in developing the Sumber Gempong Rice Field Tourism as an effort to improve the economy and empower the community in Ketapanrame Village, Mojokerto. Method: This study uses descriptive qualitative with data collection techniques through in-depth interviews, observation and documentation. Research informants include the BUMDes director, the Village Head, as well as visitors and tourism business actors who are directly involved in destination management. Results: The results of the Mutiara Welirang BUMDes strategy in developing the Sumber Gempong Rice Field Tourism show that the institutional strategy has succeeded in strengthening the organizational structure and collaboration with the community to increase active citizen participation. In the program strategy indicator, the implementation of a structured plan involving synergy between BUMDes, the village government, and the community has succeeded in increasing Village Original Income through empowering the community as MSME actors, workers, and investors. However, there are still obstacles such as visitor fluctuations and facility optimization that need to be addressed so that this tourist destination develops more sustainably and provides wider economic benefits. Novelty: The novelty of this study lies in the comprehensive application of Jack Kooten's strategy theory in the context of village tourism management and the disclosure of real obstacles in the field. This research provides an important contribution to the development of a village tourism-based economic empowerment model and the formulation of policies to optimize the role of BUMDes in local development.